PENGARUH JUMLAH PENDUDUK, ANGKA HARAPAN HIDUP, RATA-RATA LAMA SEKOLAH DAN PDRB PER KAPITA TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI BALI - Handayani, Putu Novi Sri; Bendesa, I K.G; yuliarmi, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Economic growth can be used for the welfare of certain areas. The higher the economic growth of a region assumed to residents living in the area more prosperous. Bali province has always increased economic growth in 2006 unless economic growth slowdown caused by the influence of the global crisis. The study consists of three exogenous variables, namely the number of the population, life expectancy and the average length of the school, the intervening variables Per capita GRDP and the endogenous variables of economic growth. The data used in this study of the years 2004-2013 which consists of 10 data points and multiplied by 9 districts / cities. The data is collected, analyzed using descriptive analysis and path analysis in accordance with the framework of researchers, with the AMOS program. This study aims to: 1). to analyze the influence of the population, life expectancy, the average length of the school, the GDP at constant prices on economic growth, 2). to analyze the influence of the population, life expectancy, the average length of the school to the GDP per capita at constant prices in Bali, 3). to analyze the influence of the population, life expectancy, the average length of the school to economic growth indirectly through the GDP per capita at constant prices in the province of Bali.
Keywords: population, the average length of the school, the GDP per capita, economic growth